Pelatihan Canva Untuk Guru-Guru Di SMA Swasta Amir Hamzah Medan Sumatera Utara - Gunawan, Gunawan; Lubis, Arif Ridho; Kadri Yusuf; Achmad Yani (Jurnal Masyarakat Indonesia (Jumas), 2024)
In order to improve the quality of teaching and learning activities and the competence of teachers, teachers must make teaching materials with computer media such as presentation slides and learning videos. The solution offered is to provide training for teachers to be more competent in making interactive teaching materials using computer program media, namely Canva. The proposed Community Partnership Service target is Amir Hamzah Medan private high school located on Jl. Meranti no.1, Sekip Village, Medan Petisah District, Medan Municipality, North Sumatra Province. The output produced is publication on mass media and video on social media.